Changes of the eSheath Outer Dimensions Used for Transfemoral Transcatheter Aortic Valve Replacement. (23rd April 2015) - Koehler, Till; Buege, Michael; Schleiting, Heinrich; Seyfarth, Melchior; Tiroch, Klaus; Vorpahl, Marc
Abstract : Innovative catheter systems with lower-profile sheaths and a dynamic expansion mechanism (DEM) were recently introduced for transcatheter aortic valve replacement (TAVR). However, the labeling of 14 F and 16 F eSheaths denote the inner nominal diameter. Exact changes of the clinically relevant outer diameters during usage are not available. eSheaths were measured every 30 mm using a digital caliper. Unused 14 F and 16 F eSheaths served as controls. Maximum eSheath diameters were measured after insertion of the Edwards Commander Delivery System (ECDS) into 14 F and 16 F eSheaths.Finally, eSheaths were retrieved and measured after TAVR. Outer diameters of control 14 F eSheaths were 5.8 mm and 6.50 mm for the 16 F eSheath. Introduction of the 23 mm and 26 mm ECDS into 14 F eSheaths showed a maximum diameter of 7.65 mm and 7.64 mm (P = NS ). Introduction of the 29 mm ECDS into the 16 F eSheath showed the greatest diameter of 8.18 mm (P = 0.03 ). After TAVR, diameters of the 14 F eSheaths were 7.14 mm (23 mm valve) and 7.26 mm (26 mm valve) (P = NS ), while 16 F eSheaths were 8.10 mm (29 mm valve) (P ≤ 0.03 ). Nominal 14 F and 16 F eSheaths showed a significant increase of the outer diameter during advancement of the ECDS and after TAVR implantation.